My first baby animals bedtime storybook - Ibrahim, Dalia Mohamed (Giza, Egypt Nahdet misr, 2024)
This sweet and snuggly collection of stories features the adorable baby animals from your favorite Disney Classics
The Aristocats : The birthday wish -- 101 Dalmatians : Thunderbolt patch -- Lady and the tramp : A Trusty babysitter -- Disney bunnies : Thumper's summer day -- The lion king : Wild night out -- Dumbo : Dumbo's snow day
English stories
Keywords: English stories